Same Actor in Different Stages: Genes in Shoot Apical Meristem Maintenance and Floral Meristem Determinacy in Arabidopsis - Chang, Wenwen; Guo, Yinghui; Zhang, Hao; Liu, Xigang; Guo, Lin (Frontiers in Ecology and Evolution, 2020)
Plant meristems are responsible for producing all post-embryonic organs during organogenesis. While the shoot apical meristem (SAM) maintains its meristematic property throughout the life of a plant, the floral meristem (FM) undergoes precise processes of initiation, maintenance and termination to ensure proper reproductive development and metagenesis. Plant meristem maintenance and termination are controlled by hierarchical genetic networks. While most of the genes in these networks have specific roles in particular processes, some genes have dual roles in SAM maintenance and FM termination through their interactions with different partners. Here, we summarize the molecular mechanisms of these dual-function regulators important for both SAM maintenance and FM termination. Moreover, we discuss the expansion and diversification of homeobox factors in plants, an area of research that may serve as a model or guide for future comparative analyses of meristem-related genes in diverse plant species.